Risk Factors for Acquired Stenotrophomonas maltophilia Pneumonia in Intensive Care Unit: A Systematic Review and Meta-Analysis - Wang, Neng; Tang, Congchen; Wang, Lichun (Frontiers in Medicine, 2022)
Background & Aims: Stenotrophomonas maltophilia is increasingly identified in critically ill patients, but it is considered a pathogen with limited pathogenicity and it is therefore infrequently targeted. We systematically evaluated risk factors for S. maltophilia pneumonia in ICU patients for better clinical management of these patients. Methods: the prospective and retrospective studies of S. maltophilia infection in ICU from the establishment of the database to August 8, 2021 were searched by PubMed, web of science, Cochrane Library Embase and CNKI. Based on the inclusion and exclusion criteria, two reviewers independently screened and extracted literature for quality evaluation using the NOS scale and meta-analysis by stata 14.0 software. Results: a total of 8 studies were included, with a sample size of 2320 cases. Meta-analysis showed that APACHE-II score > 20 (OR = 10.98, 95% CI: 5.67 ~ 21.26), COPD (OR = 3.97, 95% CI: 2.39 ~ 6.61), malignant tumor (OR = 2.15, 95% CI: 1.03 ~ 4.50), mechanical ventilation (OR = 8.75, 95% CI: 2.59 ~ 29.58), tracheotomy (OR = 6.12, 95% CI: 2.06 ~ 18.18), endotracheal intubation (OR = 4.25, 95% CI: 2.30 ~ 7.84), use β- Lactamase inhibitors (OR = 9.98, 95% CI: 1.51 ~ 65.96), aminoglycosides (OR = 4.01, 95% CI: 2.06 ~ 7.80), carbapenems (OR = 2.82, 95% CI: 1.49 ~ 5.31), quinolones (OR = 2.17, 95% CI: 1.21 ~ 3.89)Antibiotics are the risk factors for ICU-acquired S. maltophilia pneumonia. Conclusion: Many risk factors are associated with S. maltophilia pneumonia in ICU patients. Care should be taken in clinical work to assess the risk of infection in patients and to enhance the management of high-risk groups, which will help ICU patients to reduce the risk of infection with S. maltophilia.